Effect of short-term yoga-based lifestyle intervention on plasma glucose levels in individuals with diabetes and pre-diabetes in the community. (December 2017) - V., Venugopal; Rathi, Amit; Raghuram, Nagarthna
Abstract: Aim: To study the effect of short term Yoga-based lifestyle intervention in the management of diabetes and pre-diabetes, through a 'pilot' community-based study. Methods: A total of 1292 subjects with diagnosed type 2 diabetes and pre-diabetes were recruited from different States of India viz ., Karnataka, Maharashtra, Gujarat, Rajasthan, and Tamilnadu participated in the study. Yoga-based lifestyle intervention was introduced through 10-day non-residential camps. Baseline and post intervention assessments of fasting plasma glucose (FPG) were measured on the first day and tenth day respectively. Of 1292 subjects, 896 both pre- and post- FPG readings were available. Data analysis was done using statistical package for the social sciences (SPSS), version 16. Results: Mean baseline FPG level was 133.1 (±47.98) and the mean post intervention FPG reduced to 121.19 (±40.56). There was a statistically significant decrease in FPG, p value (<0.0001). Conclusion: The result suggests that a short-term Yoga-based lifestyle intervention effectively reduces FPG levels in type 2 diabetes patients and pre-diabetes.